A review of business models for access to affordable and clean energy in Africa: Do they deliver social, economic, and environmental value?. (June 2022) - Mukoro, Velma; Sharmina, Maria; Gallego-Schmid, Alejandro
Abstract: Africa has the potential to base a significant proportion of its development on renewable energy. Business models will be instrumental to this end because they are among the key drivers of the energy sector's growth. This study performs the first systematic literature review of renewable energy business models in Africa to assess their types, why they are adopted, and factors affecting their viability. It also investigates whether the value created translates into social, economic, and environmental sustainability. Findings show that existing research has focused on the technical, social, and economic dimensions of renewable energy business models, mainly for energy access, without analysing their environmental sustainability. The commercial viability of the business models for solar home systems and pico systems in the reviewed studies rests largely on reducing their upfront cost through innovative payment plans for customers. The commercial viability of mini-grids depends on demand stimulation, for example through encouraging end-users to start businesses that benefit from electrification projects. Incentivising the adoption of energy-using products further increases the average consumption and revenue per user and, hence, the viability of mini-grids. Unaffordability, unmet energy needs, low demand for electricity, lack of finance, business models that are unfamiliar to customers, and market immaturity are the common challenges to energy access in Africa. Our review shows that research in this area needs to integrate environmental sustainability for a more holistic approach to informing decision-making. The synthesised evidence provided here can be used by policymakers to understand the needs of Africa's renewable energy sector across the three sustainability domains. Graphical abstract: Unlabelled Image Highlights: Business models for energy access are the most common in literature on Africa. Affordability, satisfaction & community participation are key to social value of business models. Incumbent business models are insufficient to deliver the social value. Environmental impacts of business models are a research gap.